1989
DOI: 10.1002/mpo.2950170309
|View full text |Cite
|
Sign up to set email alerts
|

An animal model to detect the neuropsychological toxicity of anticancer agents

Abstract: The unexpected discovery that certain chemotherapeutic agents used in the treatment of childhood cancers have neurocognitive side effects has prompted a search for techniques that identify those medications that place children at risk. An animal model for the assessment of resultant neurocognitive toxicity is described which makes use of simple classical conditioning. We have shown that rats learn about environmental events more slowly following neonatal administration of methotrexate. The changes after methot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Sieklucka-Dziuba et al reported an impairment of long-term memory in the passive avoidance task 14 days after a single dosage of MTX injected intraperitoneal in Albino Swiss mice [40]. Moreover, Yanovksi et al showed in Lewis-inbred rat pups impaired learning of environmental events in a conditioned emotional response task and conditioned taste aversion task after a single neonatal intraperitoneal MTX injection [46]. Shors et al treated male Sprague-Dawley rats with the anti-mitotic MAM for 14 days and found a distinct decrease in BrdU positive cells in the dentate gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…Sieklucka-Dziuba et al reported an impairment of long-term memory in the passive avoidance task 14 days after a single dosage of MTX injected intraperitoneal in Albino Swiss mice [40]. Moreover, Yanovksi et al showed in Lewis-inbred rat pups impaired learning of environmental events in a conditioned emotional response task and conditioned taste aversion task after a single neonatal intraperitoneal MTX injection [46]. Shors et al treated male Sprague-Dawley rats with the anti-mitotic MAM for 14 days and found a distinct decrease in BrdU positive cells in the dentate gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…MTX-treated animals failed to display a taste aversion following the first trial, compared to controls, but were equal to controls by the second trial. Given the above results, it was concluded that neonatal rats administered MTX were slower to learn about environmental events 58. In contrast, no impairments were found in 17-day-old rat pups treated with MTX (0.005 mg/kg, i.p.)…”
Section: Rodent Models Of Childhood Cancer Treatmentmentioning
confidence: 85%
“…With an average lifespan of about two years, rodents allow effects to be studied within a developmental framework as well. Although many past studies involving chemotherapeutic agents and rodent models have involved drug administration of a single agent 56,57,58, rodent models make it possible to study drug combinations, thus providing a more accurate model of current protocols for childhood cancer treatment. Underlying mechanisms of chemotherapy-induced neurotoxicity such as decreased cell proliferation can only be studied using preclinical models.…”
Section: The Benefits Of Preclinical Rodent Modelsmentioning
confidence: 99%
“…Tasks such as contextual fear conditioning, eyeblink conditioning, passive (inhibitory) avoidance and autoshaping have been utilized to assess the impact of chemotherapeutic agents on associative learning and memory. Neonatal exposure to methotrexate can impair the development of conditioned emotional responding when assessed in young animals [144]. In adult animals, a single exposure to oxaliplatin and 5-fluorouracil results in deficits in contextual fear contitioning 4 weeks following exposure [131] and repeated exposure to cyclophosphamide and doxorubicin leads to impairments in contextual fear conditioning that persist for at least 1 week following the final exposure [145].…”
Section: Associative Learning and Memorymentioning
confidence: 99%